2023
DOI: 10.1021/acs.chemmater.3c01293
|View full text |Cite
|
Sign up to set email alerts
|

Photoconversion of Ag31 to Ag42 Initiated by Solvated Electrons

Arijit Jana,
Wakeel Ahmed Dar,
Sourav Kanti Jana
et al.

Abstract: Light-matter interactions, especially in atomically precise nanomaterials, belong to an unexplored realm of research with potential benefits for the synthesis of materials. Here, we present an interesting light-activated expansion process of an Ag 31 nanocluster to an Ag 42 analogue, both clusters being protected with 6-(dibutylamino)-1,3,5-triazine-2, 4-dithiol (shortly, TRZ-H 2 ) ligands. The conversion process was initially monitored through UV−vis, revealing that the violet-colored Ag 31 got converted to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Physical stimuli, including light irradiation, temperature, electricity, and pressure, play a role in activating the chemical flexibility of metal clusters . Light irradiation easily excites electron transitions in metal clusters, especially when combined with other factors in a solution, thereby initiating reactions of the metal clusters. , Elevated temperatures can modify bond lengths, affecting the overall thermodynamics of cluster formation, and increase the kinetic energy of molecules, inducing phase transitions that potentially lead to complete reconstruction. The application of an electric field or current can drive electrochemical reactions involving metal clusters. Under high-pressure conditions, there can be changes in bond lengths, coordination environments, and even phase transitions. Understanding the pressure dependence of cluster stability is crucial for applications in extreme environments. In section , this Review will explore the structural changes and associated properties of metal clusters under various physical conditions, closely aligning with potential future application environments.…”
Section: Physical Inducement-triggered Reactionsmentioning
confidence: 99%
“…Physical stimuli, including light irradiation, temperature, electricity, and pressure, play a role in activating the chemical flexibility of metal clusters . Light irradiation easily excites electron transitions in metal clusters, especially when combined with other factors in a solution, thereby initiating reactions of the metal clusters. , Elevated temperatures can modify bond lengths, affecting the overall thermodynamics of cluster formation, and increase the kinetic energy of molecules, inducing phase transitions that potentially lead to complete reconstruction. The application of an electric field or current can drive electrochemical reactions involving metal clusters. Under high-pressure conditions, there can be changes in bond lengths, coordination environments, and even phase transitions. Understanding the pressure dependence of cluster stability is crucial for applications in extreme environments. In section , this Review will explore the structural changes and associated properties of metal clusters under various physical conditions, closely aligning with potential future application environments.…”
Section: Physical Inducement-triggered Reactionsmentioning
confidence: 99%
“…In a recent study, the same group observed a light-activated size-expansion process, wherein the [Ag 31 (TRZ) 10 ] 2−/1− cluster transformed into the [Ag 42 (TRZ) 13 ] 2+ cluster (TRZ: 6-(dibutylamino)-1,3,5-triazine-2,4-dithiolate). 87 The size conversion was demonstrated using absorption spectroscopy of NCs with fingerprint absorption features, as well as a clear color change from violet to greenish. The Ag 31 cluster exhibits photoresponsive behavior, and the resulting intermediate species are covered with solvated electrons, contributing to the expansion of the cluster size.…”
Section: Transformation and Surface Reactivitymentioning
confidence: 99%